INTERNALISASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM MELALUI KEGIATAN PRAMUKA DALAM MEMBENTUK AKHLAK TOLERAN SISWA DI SMP NOOR MUSHOLLA SURABAYA - Bachtiar Hariadi; Chusnul Alifah; M. Yahya; Lis Ma'rifah; Istirohah (Journal Multicultural of Islamic Education, 2023)
This study explores the effectiveness of implementing Internalization of Islamic Education Values through Scout Activities in Fostering Tolerant Character among students at SMP Noor Musholla Surabaya. Employing a qualitative approach, the research examines the planning and execution of scout programs, focusing on the integration of Islamic values and the internalization process. Tri Satya serves as the foundational principle, emphasizing the importance of tolerance. The study concludes that scout activities, facilitated by dedicated scout leaders, play a pivotal role in nurturing tolerant behavior among students. This research contributes valuable insights into character development within an Islamic educational context through the qualitative exploration of scout activities.